Constructivist Communicative Strategies for Integration of Communication Skills in Grammar Classroom (Czech Journal of Multidisciplinary Innovations, 2022)
The purpose of this study is to examine approaches used by the teachers in Mapoteng high school to improve reading, writing and speaking skills in teaching of English grammar. The study further objects to identify activities that incorporate and reflect to constructivist communicative approach to improve the learners’ communication skills. The study is framed by the Constructivist Communicative Approaches. Following the qualitative case research approach, data was purposely and conveniently collected from 37 Form D learners and 4 language teachers using observation, unstructured interview, learners’ records of scores on teacher-made tests and reflective self-evaluation from lesson plan. The results reveal that due inadequate time and resources, as well as demotivated learners, most of the teachers use mainly the traditional methods. However, the study also divulges that both traditional grammar and communicative approaches would at least be used together to complement each other. The results further reveals that the learners who learn grammatical aspects through reading, turn to improve in reading and writing skills. The study concludes that the use of authentic material such as different texts in class improves the learners’ use of words in context; and this lead to sociolinguistics competence. This study also concludes that teaching of English grammar on the basis of constructivist communicative approach triggers active participation in class, and that leads to second language acquisition as well as improved performance. Activities such as watching movies, reading, discussing and dramatizing on local and global issues enhance constructivist communicative approach.